PLANT GROWTH PROMOTING TRAITS OF RHIZOBACTERIA ISOLATED FROM POTATO (Solanum tuberosum L.) AND THEIR ANTIFUNGAL ACTIVITY AGAINST Fusarium oxysporum - S. Jadoon; A. Afzal; S. A. Asad; T. Sultan; T. Tabassam; M. Umer; M. Asif (Journal of Animal and Plant Sciences, 2019)
Rhizosphere bacteria are known to augment plant growth and suppress plant diseases. Current study was designed to evaluate the plant growth promoting and disease suppressing traits of indigenous bacteria from the rhizosphere of potato, Solanum tuberosum. For this purpose, out of 160 isolates, 20were further investigated to determine their ability for producing hydrogen cyanide (HCN), ammonia (NH3), indole 3-acetic acid (IAA), lytic enzymes, solubilize phosphate and antagonize Fusarium oxysporum. Results revealed that 12 isolates were able to solubilize phosphate thereby creating halo zone between 1.00-2.40 mm, where PRP-6 caused maximum solubilization. Three strains, PRP-6, PRS-17 and PRS-24 were able to produce IAA, but the concentration was significantly different (p<0.01) from each other. Majority of the isolates exhibited strong potential (++) for producing NH3 and HCN. Lytic enzymes production trait was observed in 83% of isolates but with varying potentials (weak, medium, strong). Overall, the percentage growth inhibition of F. oxysporum by bacterial isolates ranged from 13-46%, where PRP-6, PRP-13displayed maximum and minimum antagonistic potential respectively. Our results indicate that novel strains from the potato rhizosphere exhibit the plant growth promoting rhizobacteria (PGPR) traits which could be used for the development of potato biofertilizers and as biocontrol agents to antagonize F. oxysporum.
Keywords: PGPR; Biocontrol; Solanum tuberosum; Fusarium oxysporum